Pre, During and Post Covid-19 Stock Returns and Volatility Comparison: - Dr Nawaz Ahmed; Ramsha Nazeer; Amira Kaddour (International Journal of Experiential Learning & Case Studies, 2024)
This study aims to study the pre, during and post-COVID-19 stock returns and volatility associated with Pakistan. For this study, daily financial data from 2018 to 2023. This study is based on daily prices and their returns. The data was divided into categories like Category A: Before the COVID-19 pandemic, Category B: during the COVID-19 pandemic and Category C: Post COVID-19 pandemic. The indices period is from 1st January 2018 to 25th February 2020 (Pre Covid-19), 26th February 2020 to 31st December 2021 (during Covid-19) and from 1st March 2022 to 8th May 2023 (Post Covid-19) period. The data were treated with Descriptive and Econometric Models using E-views, Microsoft Excel and SPSS. The findings of this research are that there is no stationarity issue in all the returns’ series, and the average return for Pre (Category A) and Post Covid periods (Category C) is positive; however, it is negative During the Covid period (Category B) which shows the bearish trend in Pakistan Stock Exchange market (PSX) due to the Covid-19 outbreak. Moreover, the coefficient of variation (CV) is computed, which shows that pre-COVID tenure has the highest relative dispersion (CV = 44.43), followed by during COVID (CV = 40.76), and post-COVID tenure has the most negligible coefficient of relative dispersion (CV = 23.1) which refers to the least volatile phenomenon. The findings also suggest no statistically significant difference among all average returns, and all are equal. The results from the econometric model show that the highest mean reversion value was 0.969991 During the COVID period. Post-COVID has a value of 0.449377, which indicates the quick mean reversion compared to the other two.